(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article delves into the intricate relationship between foreign trade and economic growth, employing a robust statistical research framework to unravel the underlying dynamics. Grounded in foundational economic theories such as comparative advantage and absolute advantage, the study explores how nations strategically leverage international trade to bolster their economic prosperity. Modern economic paradigms, including endogenous growth theory and new trade theory, further enrich the theoretical foundations, offering contemporary perspectives on the role of foreign trade in fostering sustainable development.